2018
DOI: 10.2147/jir.s140188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of NF-κB p65 and strategies for therapeutic manipulation

Abstract: The transcription factor NF-κB is a critical regulator of immune and inflammatory responses. In mammals, the NF-κB/Rel family comprises five members: p50, p52, p65 (Rel-A), c-Rel, and Rel-B proteins, which form homo- or heterodimers and remain as an inactive complex with the inhibitory molecules called IκB proteins in resting cells. Two distinct NF-κB signaling pathways have been described: 1) the canonical pathway primarily activated by pathogens and inflammatory mediators, and 2) the noncanonical pathway mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
310
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(320 citation statements)
references
References 130 publications
(221 reference statements)
9
310
0
1
Order By: Relevance
“…The primary consequences of oxidative stress include fragmentation of lipids or structural changes thereof, protein denaturation, disorders related to the DNA replication mechanisms, and deformation of cellular organelles, and consequently, entire cells ( Figure 1). ROS-induced oxidative stress leads not only to inflammation but also triggers the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) protein-dependent transcription of genes for various proinflammatory factors [28]. The activity of ROS leads to various types of intracellular damage, including enzyme activation, DNA damage, structural changes in protein and carbohydrate molecules.…”
Section: Oxidative Stress As the Primary Cause Of Brain Damagementioning
confidence: 99%
“…The primary consequences of oxidative stress include fragmentation of lipids or structural changes thereof, protein denaturation, disorders related to the DNA replication mechanisms, and deformation of cellular organelles, and consequently, entire cells ( Figure 1). ROS-induced oxidative stress leads not only to inflammation but also triggers the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) protein-dependent transcription of genes for various proinflammatory factors [28]. The activity of ROS leads to various types of intracellular damage, including enzyme activation, DNA damage, structural changes in protein and carbohydrate molecules.…”
Section: Oxidative Stress As the Primary Cause Of Brain Damagementioning
confidence: 99%
“…In sum, Ala demonstrates anti-neuroinflammatory properties that contribute to the amelioration of CNS damage, and it could be a promising candidate for future applications in CNS injury treatment.be found that two signaling pathways stand out as being strongly associated with the production of proinflammatory factors: Nuclear factor kappa light-chain enhancer of activated B cells (NF-κB) [10] and mitogen-activated protein kinase (MAPK) [11].Because it is responsible for the transcription of several proinflammatory cytokines, chemokines, and adhesion molecules, the NF-κB signaling pathway plays a crucial role in many diseases that involve dysregulation of the inflammatory response [12,13]. The NF-κB signaling pathway consists of a series of intracellular secondary reactions [14,15]. First, extracellular stimuli give rise to the phosphorylation and proteasomal degradation of the nuclear factor of the kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) [16,17].…”
mentioning
confidence: 99%
“…Because it is responsible for the transcription of several proinflammatory cytokines, chemokines, and adhesion molecules, the NF-κB signaling pathway plays a crucial role in many diseases that involve dysregulation of the inflammatory response [12,13]. The NF-κB signaling pathway consists of a series of intracellular secondary reactions [14,15]. First, extracellular stimuli give rise to the phosphorylation and proteasomal degradation of the nuclear factor of the kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) [16,17].…”
mentioning
confidence: 99%
“…NF-κB is retained in an inactive form in the cytoplasm in most cell types [51]. When it is activated, NF-κB translocates to the nucleus and plays a critical role in activating the inflammatory signaling network [52]. Our previous study found that NF-κB activation contributes to the inflammatory responses in human AVICs [44].…”
Section: Discussionmentioning
confidence: 96%